Security Design In Doors And Windows Arduino Based Using Fingerprint And Sms Gateway (Case Study At Pesona Asri Tembalang Housing) - Siska Setiani; Bagus Sudirman (University of Science and Computer Technology, 2023)
This research discusses security design for Arduino-based doors and windows using fingerprint technology and SMS Gateway. The case study was conducted at Pesona Asri Tembalang Housing. The main goal of this research is to improve household security by combining fingerprint authentication technology and text messaging (SMS) as a safer and more efficient access mechanism.This system development method includes analyzing household security needs, designing an Arduino-based system, integrating fingerprint modules and SMS Gateway, as well as testing and evaluating system performance. The research results show that this system is able to provide a high level of security with accurate fingerprint authentication and direct notification via SMS Gateway when suspicious activity occurs.In conclusion, an Arduino-based door and window security design with fingerprint technology and SMS Gateway is an effective solution for increasing household security. Implementing these systems can help reduce the risk of intrusion and give homeowners better control over access to their property.